Integration of naturally bioactive thiazolium and 1,3,4-oxadiazole fragments in a single molecular architecture as prospective antimicrobial surrogates - Huai-He Zhu; Dan Zeng; Ming-Wei Wang; Pei-Yi Wang; Yuan-Yuan Wu; Li-Wei Liu; Song Yang (Journal of Saudi Chemical Society)
Plant microbial diseases caused global production constraints have become one of the most challenging events, thus urgently needing to be addressed nowadays. To efficiently promote the discovery of promising antimicrobial surrogates, a type of 1,3,4-oxadiazole thioethers owning naturally bioactive thiazolium patterns was designed and fabricated. Antibacterial screening results revealed that title compounds could significantly inhibit the growth of pathogens Xanthomonas oryzae pv. oryzae, Ralstonia solanacearum, and Xanthomonas axonopodis pv. citri. And the related antibacterial efficacy was elevated by approximately 386-, 16-, and 24-folds comparing those of mainly used commercial agents bismerthiazol and thiodiazole copper. In vivo experiment suggested that A9 could manage rice bacterial blight with the corresponding curative and protection efficiencies of 48.01% and 50.55% at 200 μg/mL. Moreover, SEM patterns and fluorescence spectra were performed to explore the possible antibacterial mechanism. Preliminary antifungal bioassays revealed that these molecules paraded broad-spectrum inhibition effects against three tested fungal strains. Considering the simple molecular skeleton and significant biological actions, title compounds can be further explored as potential antimicrobial surrogates for managing plant bacterial and fungal diseases. Keywords: Thiazolium, 1,3,4-Oxadiazole, In vitro and in vivo bioassays, Antimicrobial